Implementation of wheelchair motion control based on electrooculography using simulation and experimental performance testing - Mohd Noor, Nurul Muthmainnah; Ahmad, Salmiah; Sidek, Shahrul Na'im (Trans Tech Publications Ltd., Switzerland, 2014)
The aim of this study is to perform the experimental verification on the fuzzy-based control designed for wheelchair motion. This motion control based on the eye movement signals using electrooculograhphy (EOG) technique. The EOG is a technique to acquire the eye movement data from a person, i.e tetraplegia, which the data obtained, can be used as a main communication tool. This study is about the implementation of the designed controller using PD-type fuzzy controller and tested on the hardware of the wheelchair system using the eye movement signal obtained through EOG technique as the motion input references. The results obtained show that the PD-type fuzzy logic controller designed has successfully managed to track the input reference for linear motion set (forward and backward direction) by the EOG signal.